Comparison of drug coverage in Canada before and after the establishment of the pan-Canadian Pharmaceutical Alliance. Issue 9 (4th September 2015) - Milliken, Debbie; Venkatesh, Jaya; Yu, Rebecca; Su, Zhuo; Thompson, Melissa; Eurich, Dean
Abstract : Objectives: This study was conducted to determine whether establishment of the pan-Canadian Pharmaceutical Alliance (pCPA) was associated with significant changes in drug listing decisions across Canada. Analysis and results: This study included drug indications that received a Common Drug Review or pan-Canadian Oncology Drug Review listing recommendation within 3 years before ('pre-PCPA era' group; n=79) and 3 years after ('PCPA era' group; n=91) the pCPA was established in August 2010. At the time of this study (30 April 2014), nine pCPA-participating jurisdictions had listed 35–59% of drug indications in the pre-pCPA era group and a nearly identical range, 36–59%, in the pCPA era group. Within the pCPA-era group, 31 drug indications (34%) had completed pCPA negotiations ('pCPA negotiation' subgroup); the jurisdictions had listed 39–77% of these drug indications. Comparison of the pCPA era group to the pre-pCPA era group indicated that the proportion listed did not change significantly in any jurisdiction, and time-to-listing increased significantly in New Brunswick and decreased significantly in Alberta, Manitoba, and Ontario. When the pCPA negotiation subgroup was compared to the pre-pCPA era group, the proportion listed increased significantly in British Columbia, Saskatchewan, Manitoba and Newfoundland and Labrador, and time-to-listing increased significantly in New Brunswick and Nova Scotia and decreased significantly in Manitoba and Ontario. A sensitivity analysis suggested more favourable results regarding the pCPA's impact. Conclusions: While the pCPA might have had a varied effect on time-to-listing, this study's primary analysis did not observe a significant impact on the overall proportion of new drug indications listed across jurisdictions. This may be due to the fact that, at the time of this study, only a limited number of drug indications had completed pCPA negotiations. This study provides a framework for future evaluations of the pCPA's impact as it continues to evolve.